Biomechanical Head-to-Head Comparison of 2 Sutures and the Giftbox Versus Bunnell Techniques for Midsubstance Achilles Tendon Ruptures - Van Dyke, Rufus O. (Orthop J Sports Med, 2017)
BACKGROUND: Acute midsubstance Achilles tendon ruptures are a common orthopaedic problem for which the optimal repair technique and suture type remain controversial. Head-to-head comparisons of current fixation constructs are needed to establish which stitch/suture combination is most biomechanically favorable. HYPOTHESIS: Of the tested fixation constructs, Giftbox repairs with Fiberwire will exhibit superior stiffness and strength during biomechanical testing. STUDY DESIGN: Controlled laboratory study. METHODS: Two biomechanical trials were performed, isolating stitch technique and suture type, respectively. In trial 1, 12 transected fresh-frozen cadaveric Achilles tendon pairs were randomized to receive either the Giftbox-modified Krackow or the Bunnell stitch with No. 2 Fiberwire suture. Each repair underwent cyclic loading, oscillating between 10 and 100 N at 2 Hz for 1000 cycles, with repair gapping measured at 500 and 1000 cycles. Load-to-failure testing was then performed, and clinical and catastrophic failure values were recorded. In trial 2, 10 additional paired cadaveric Achilles tendons were randomized to receive a Giftbox repair with either No. 2 Fiberwire or No. 2 Ultrabraid. Testing and data collections protocols in trial 2 replicated those used in trial 1. RESULTS: In trial 1, the Bunnell group had 2 failures during cyclic loading while the Giftbox had no failures. The mean tendon gapping after cyclic loading was significantly lower in the Giftbox repairs (0.13 vs 2.29 mm, P = .02). Giftbox repairs were significantly stiffer than Bunnell (47.5 vs 38.7 N/mm, P = .019) and showed more tendon elongation (5.9 ± 0.8 vs 4.5 ± 1.0 mm, P = .012) after 1000 cycles. Mean clinical load to failure was significantly higher for Giftbox repairs (373 vs 285 N, P = .02), while no significant difference in catastrophic load to failure was observed (mean, 379 vs 336 N; P = .61). In trial 2, there were no failures during cyclic loading. The Giftbox + Fiberwire repairs recorded higher clinical load-to-failure values compared with Giftbox + Ultrabraid (mean, 361 vs 239 N; P = .005). No other biomechanical differences were observed in trial 2. CONCLUSION: Simulated early rehabilitation biomechanical testing showed that Giftbox-modified Krackow Achilles repair technique with Fiberwire suture was stronger and more resistant to gap formation at the repair site than combinations that incorporated the Bunnell stitch or Ultrabraid suture. CLINICAL RELEVANCE: A more in-depth understanding of the biomechanical properties of the Giftbox repair will help inform surgical decision making because stronger repairs are less likely to fail during accelerated postoperative rehabilitation.